1988
DOI: 10.1577/1548-8675(1988)008<0210:eoydiw>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Even-Odd Year Differences in Walleye Year-Class Strength Related to Mayfly Production

Abstract: Young-of-the-year walleyes Stizostedion vitreum are more abundant in even-numbered years than in odd-numbered years in Savanne Lake, Ontario. Differences among years were related to emergences of the burrowing mayfly Hexagenia limbata. Adult walleyes from evennumbered year classes are more abundant than those from odd-numbered year classes. We hypothesize that pulse production of H. limbata in even-numbered years positively affects walleye recruitment by enhancing egg production by adult walleyes and buffering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 13 publications
1
18
1
Order By: Relevance
“…During this period, YOY walleye were rarely found in habi- tats that provided little or no cover. The utilization of heavily vegetated habitats was opposite to our predictions, as previous research had suggested that young walleye prefer more open habitats (Savoie 1983;Ritchie and Colby 1988;Lane et al 1996) and should avoid vegetation to reduce the threat of largemouth bass predation (Santucci and Wahl 1993). It is possible that previous researchers who classified YOY walleye as habitat generalists may have missed the short time period where young walleye utilized high cover areas, as it occurred immediately after the pelagic phase and the fish were residing in areas difficult to sample using most traditional sampling gear.…”
Section: Habitat Usecontrasting
confidence: 99%
See 2 more Smart Citations
“…During this period, YOY walleye were rarely found in habi- tats that provided little or no cover. The utilization of heavily vegetated habitats was opposite to our predictions, as previous research had suggested that young walleye prefer more open habitats (Savoie 1983;Ritchie and Colby 1988;Lane et al 1996) and should avoid vegetation to reduce the threat of largemouth bass predation (Santucci and Wahl 1993). It is possible that previous researchers who classified YOY walleye as habitat generalists may have missed the short time period where young walleye utilized high cover areas, as it occurred immediately after the pelagic phase and the fish were residing in areas difficult to sample using most traditional sampling gear.…”
Section: Habitat Usecontrasting
confidence: 99%
“…YOY walleye completely abandoned the middepth vegetated habitat and moved to shallower habitats with less available cover. The move to areas with reduced cover fits the traditional view of YOY walleye habitat selection (Savoie 1983;Ritchie and Colby 1988;Lane et al 1996), but the selection of primarily shallow water (<2 m depth) suggests that YOY walleye may not be as affected by high light levels as older individuals (Ryder 1977). Other studies have found YOY walleye at depths of up to 10 m by the fall (Raney and Lachner 1942), and while the intensive component of this study ended in August, periodic SCUBA observations that extended into October indicated that most YOY walleye were still in shallow, low-cover habitats at that time.…”
Section: Habitat Usementioning
confidence: 64%
See 1 more Smart Citation
“…As zebra mussels colonize soft sediments, they have the potential to affect the foraging success of a range of species. In particular, juveniles of some species (e.g., yellow perch, walleye, sturgeon) utilize soft sediment zoobenthos for food during critical growth periods (Ritchie and Colby 1988;Scott and Crossman 1973;Beamish et al 1998). Negative effects on already threatened or endangered species such as the lake sturgeon may have important implications for conservation and reintroduction programs.…”
Section: Discussionmentioning
confidence: 99%
“…Use of the Ponar will lead to more accurate density estimates of burrowing mayfly nymphs and possibly other benthos that are important to food webs, fish energetics, and monitoring of habitat quality (Fremling 1964, Harris et al 1987, Haywood and Margraf 1987, Ritchie and Colby 1988, Reynoldson et al 1989, Kolar et al 1997, Madenjian et al 1998, Ohio Lake Erie Commission 1998). As pollution-abatement programs continue, burrowing mayfly nymphs will undoubtedly return to sediments in other areas of the Great Lakes where they were once abundant but have been absent for decades.…”
Section: Sampler Recommendationmentioning
confidence: 99%